Translating childhood brain tumour research into clinical practice: the experience of molecular classification and diagnostics - Ritzmann, Timothy A.; Grundy, Richard G. (Elsevier, 2018)
Diagnosis and treatment of paediatric brain tumours has shown limited progress over the last half century. However, in the past 10 years the development of molecular techniques for investigating these tumours has expanded exponentially. The use of methylation profiling, gene expression analysis and the identification of gene fusions are forming the basis for improved diagnostic criteria and new treatment approaches. Knowledge and practice in this area is now beginning to expand beyond the research field and into the clinical setting. As the Chief Medical Officer highlighted in July 2017, an understanding of molecular medicine and its implications for both patients and the health economy is important for all clinicians. In this article, we summarise important recent advances in molecular medicine in childhood brain tumour research using the three most common types of paediatric brain tumour; pilocytic astrocytoma, medulloblastoma and ependymoma as illustrative examples.